MODIFIKASI MODEL PENJALARAN GELOMBANG MULTI ARAH - Marwan, Marwan (MATEMATIKA, 2009)
In this paper we derived a modification of the model of waves evolution in two-directional spatial coordinates. Using KP equation as the basic model, we improved dispersive property in spatial x coordinate and named it as improved KP (iKP) equation. iKP has an exact dispersion relation in spatial x coordinate. Using this model, we derived second order regular waves andÂ  analyzed the expression of Maximum Temporal Amplitude. Â